Addressing the Problems of Pensioners and Unemployment Insurance in UAE Law - Ayman Mohamed Zain Othman; Aisha Obaid Rashid ALqaydi (Journal of Legal Sciences, 2024)
After retirement, a pensioner’s life may raise many legal issues which social legislation endeavors to alleviate by creating flexible and fair legal rules in appreciation of the pensioners’ previous contribution to productivity. This article investigates the effectiveness of the labor legislation under the UAE pension and social security law. As the UAE legislator intends to enhance the individual’s right through insurance against the risk of unemployment, the legislator issued the Federal Decree Law No. (13) of 2022 for unemployment insurance. The decree has recently been implemented in both private and government sectors. This prompted us to analyze the legislator’s approaches in issues related to the concept of unemployment and the terms and conditions for eligibility from both jurisprudential and legislative points of view. Besides identifying the groups excluded from the application, the article aims to present the legal problems and solutions affecting the worker’s right to insurance eligibility besides unregulated points which necessitate submission of a comparative paper on judicial and legislative efforts to upgrade the law thereof. The study found some legislative deficiencies in the Unemployment Insurance Law, principally as the transfer of insurance upon the death of the unemployed worker remains unclarified. Added to a lack of alternatives when the worker’s unemployment continues for more than three months as stipulated under the decree.